Syncoilin, a novel member of the intermediate filament superfamily that interacts with alpha-dystrobrevin in skeletal muscle. - Newey, S; Howman, E; Ponting, C; Benson, M; Nawrotzki, R; Loh, N; Davies, K; Blake, D (2001)
Dystrophin coordinates the assembly of a complex of structural and signaling proteins that are required for normal muscle function. A key component of the dystrophin protein complex is alpha-dystrobrevin, a dystrophin-associated protein whose absence results in neuromuscular junction defects and muscular dystrophy. To gain further insights into the role of alpha-dystrobrevin in skeletal muscle, we used the yeast two-hybrid system to identify a novel alpha-dystrobrevin-binding partner called syncoilin. Syncoilin is a new member of the intermediate filament superfamily and is highly expressed in skeletal and cardiac muscle. In normal skeletal muscle, syncoilin is concentrated at the neuromuscular junction, where it colocalizes and coimmunoprecipitates with alpha-dystrobrevin-1. Expression studies in mammalian cells demonstrate that, while alpha-dystrobrevin and syncoilin associate directly, overexpression of syncoilin does not result in the self-assembly of intermediate filaments. Finally, unlike many components of the dystrophin protein complex, we show that syncoilin expression is up-regulated in dystrophin-deficient muscle. These data suggest that alpha-dystrobrevin provides a link between the dystrophin protein complex and the intermediate filament network at the neuromuscular junction, which may be important for the maintenance and maturation of the synapse.